VD_FINDINFO AM 74/09 - 16/2011 vom 28. Februar 2011 - VD Tribunal cantonal (2011)
PRESTATION D'ASSURANCEAM, TRAITEMENT À L'ÉTRANGER, NÉCESSITÉ D'UN TRAITEMENT | 1 al. 1 LAMal, 24 LAMal, 25 al. 1 LAMal, 25 al. 2 LAMal, 25 al. 2 let. b LAMal, 22 Règl. 1408/71